Large Anorectal Venous Malformation Treated With Microfoam Therapy. Issue 3 (31st March 2023) - Jha, Ashish Kumar; Suchismita, Arya; Dayal, Vishwa Mohan
ABSTRACT: Deficiency of smooth muscle cells can lead to dysfunction and engorgement of blood vessels termed as hemangioma, arteriovenous malformations, and venous malformations (VMs). Anorectal VM is a rare disease. It can present with massive hematochezia. An optimal treatment of anorectal VMs has not been defined. Surgery is an option if the lesion can be resected completely. Endoscopic injection sclerotherapy has been reported to be effective in treating small colorectal VMs. However, it has rarely been described in the treatment of large VMs. In this study, we describe a rare case of large anorectal VMs treated with microfoam sclerotherapy.